1979
DOI: 10.1007/bf00337296
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of orientation columns in the visual cortex

Abstract: The optimal direction of lines in the visual field to which neurons in the visual cortex respond changes in a regular way when the recording electrode progresses tangentially through the cortex (Hubel and Wiesel, 1962). It is possible to reconstruct the field of orientations from long, sometimes multiple parallel penetrations (Hubel and Wiesel, 1974; Albus, 1975) by assuming that the orientations are arranged radially around centers. A method is developed which makes it possible to define uniquely the position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 22 publications
5
75
1
Order By: Relevance
“…Braitenberg and Braitenberg (1979) have proposed a simple method to uniquely define the position of these centers on the vicinity of the electrode tracks. Their method was based on the extension of successive oriented lines corresponding to the orientation selectivity at each recording site along an electrode track.…”
Section: The Braitenberg's Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Braitenberg and Braitenberg (1979) have proposed a simple method to uniquely define the position of these centers on the vicinity of the electrode tracks. Their method was based on the extension of successive oriented lines corresponding to the orientation selectivity at each recording site along an electrode track.…”
Section: The Braitenberg's Methodsmentioning
confidence: 99%
“…Based on one-dimensional evaluation of orientation, Hubel and Wiesel (1974) suggested that the orientation preference might be represented in parallel slabs in primate visual cortex. Conventional microelectrode measurements offer a one-dimensional picture of columnar organization within a three-dimensional cortex; however, it has been difficult to deduce from such measurements the precise form of the larger two-dimensional (2D) columnar representation (Braitenberg and Braitenberg 1979).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With such descriptions, it becomes possible to identify subtle differences [for instance, that the hippocampus does not look all that different from the cortex (Braitenberg and Schüz 1983)], and to give discerning criteria between brain organs. Also the appearance of particular symmetries, such as columns in the visual cortex (Braitenberg and Braitenberg 1979) or the barrel cortex of rodents, can be explained with relation to behavior (Braitenberg 1977).…”
Section: The Primacy Of Neuroanatomymentioning
confidence: 99%